Herpesvirus associated dermal papillomatosis in Williams' mud turtle Pelusios williamsi with effects of autogenous vaccine therapy - Široký, Pavel; Frye, Fredric L; Dvořáková, Nela; Hostovský, Martin; Prokop, Hynek; Kulich, Pavel (Journal of veterinary medical science, 2018)
An adult female of Williams' mud turtle, Pelusios williamsi long-term captive, that was allegedly caught wild in Kenya was found to have developed papilloma-like skin lesions. Excised tumors were examined histologically after routine processing with hematoxylin and eosin (H & E) stained slides, examined for the presence of viral particles by electron microscopy employing negative staining, and examined for the presence of viral DNA by PCR. Microscopic features in pre-treatment biopsies were fully diagnostic and consistent with multifocal squamous cell papilloma. Viral-type inclusion bodies were not identified. Turtle was found to be infected by reptilian herpesvirus. Association with herpesvirus and vast multiplicity of tumors thwarted surgical solution. An autogenous vaccine was prepared using 5 g of excised fresh tissue, aseptically ground, treated with diluted formalin, centrifuged to obtain a supernatant, and subsequently exposed to UV light. Autogenous vaccine induced substantial areas of necrosis of the papillomatous lesions noted by the loss of cytological architecture, nuclear loss, and by edema. The outer edges of the healing biopsies appeared to be regenerating. Therefore, our vaccine application could be considered as effective. It is difficult to treat and eliminate herpesvirus infection because of its cryptic presence and sudden onset of disease. Successful application of autogenous vaccine could be a potentially promising strategy, which deserves further testing.
Keywords: ženské pohlaví; Female; autovakcíny; Papilloma; Herpesviridae; Animals; Autovaccines; Skin Neoplasms; nádory kůže; zvířata; papilom; želvy; Turtles